15. Cortical median nerve somatosensory evoked potentials (cSEP) and cortical evoked high frequency oscillations (cHFO) in patients affected by hyperkinetic disorders and cortical increased-excitability. Issue 12 (December 2017) - Curzi, S.; Franceschetti, S.; Scaioli, V.
Abstract : The cHFO has achieved increasing interest in human functional studies and pathophysiological alterations in neurological disorders. The relationships between cHFO and movement disorders and cSEP increased amplitudes are yet to be clarified. To investigate cHFO in unilateral and bilateral hyperkinetic disorders (tremor, dystonia and myoclonus) and neurological syndromes with cSEP increased excitability. cHFO (total number, amplitudes and frequency) were recorded in six patients affected by hyperkinesia and measured off-line (digital band-pass filter 500–1000 Hz) from cSEP (over Cc′ of the contralateral stimulated side), and compared with matched for age control group data: OPs' mean number = 9, mean frequency 700 Hz, total amplitude 1.35 μV. Four patients with unilateral movement disorders: cSEP were symmetrical (latency 17 ms, amplitude 7.5 μV); cHFO affected side: number = 2; total amplitude: 0.3 μV (unaffected side normal). Three case reports: a 10 yrs old with unilateral increased of cHFO (cSEP symmetrical); a 17 yrs old boy affected by cortical myoclonus, with enhanced cSEP and extinguished cHFO; a 60 yrs old men with ataxia and spastic paresis with unilateral extinguished cHFO and normal, symmetrical cSEP. cHFO and cSEP pathological increase-decrease occurred independently each other: cSEP increased amplitude with decreased cHFO and cHFO increased amplitude with normal cSEP. cHFO showed correlation with the type and side of movement disorder. Significance: a-the neuronal mechanism underlying cHFO increased-decreased and cSEP increased amplitudes occurred independently; b-cHFO changes showed positive correlation with hyperkinetic disorders, in particular of subcortical origin.